COVID-19 PEDAGOGY IN ONLINE SCHOOL FIELD INTRODUCTION PROGRAM AT JUNIOR AND SENIOR HIGH SCHOOLS IN PURWOKERTO - Erna Wardani; Indriyati Hadiningrum; Weksa Fradita Asriyama (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2022)
The Covid-19 pandemic has changed the educational process at all levels globally. Educational activities that originally took place in face-to-face activities have turned into online or network activities. This online activity also has a great influence on the ability to educate and teach teachers and students practicing School Field Introduction programs. This study aims to determine (1) the Supervising Teacher's perception of the implementation of the Online School Field Introduction Program for English Education Undergraduate students and (2) the Supervising Teacher's perception of the student's pedagogical competence during School Field Introduction programs for English Education Undergraduate students. There are 8 Junior High Schools (SMP), 7 Senior High Schools (SMA), and 2 Vocational High Schools (SMK) which are the venues for the event. This study uses a descriptive method where the researcher provides a detailed description of the perception of the supervising teacher on the implementation of the online school field introduction program and the student's pedagogical ability in the activity. The results showed that the implementation of the Online School Field Introduction Program was going well and the students' pedagogical abilities still needed to be improved in teaching and learning activities. This is evidenced by positive perceptions of campus communication points (80%), coordination and debriefing activities (86%), drop-off and withdrawal activities (82%), the mentoring process (81%), and the reporting process (80%) of a total of 50 supervising teachers as respondents. Meanwhile, in terms of students' pedagogical abilities, neutral perceptions are found in the understanding students (74%), development of high school students' potentials (70%), and understanding the educational foundation for the benefit of learning (72%). However, negative perceptions are centered on the designing and implementing learning (56%) as well as the designing and implementing evaluation (54%).